A recurrent fibrillin-1 mutation in severe early onset Marfan syndrome - Sureka, Dimple; Stheneur, Chantal; Odent, Sylvie; Arno, Gavin; Murphy, Daniel; Bernstein, Jonathan A. (Journal of Pediatric Genetics, 2014)
The recurrent substitution of isoleucine for threonine at codon 1048 (I1048T) substitution has been linked to severe, early onset Marfan syndrome, however, the existence of strong genotype-phenotype associations in Marfan syndrome (MFS) is not widely agreed upon. Our aim is to substantiate the association between the I1048T substitution and a severe clinical presentation to facilitate care planning and genetic counseling. We review the clinical findings from seven cases of early-onset MFS with a recurrent I1048T substitution. The presented findings include those from one newly diagnosed case, significant new detail from three additional cases, and a review of published findings in three cases. All seven individuals with the I1048T substitution had mitral insufficiency, arachnodactyly and characteristic facies consistent with early-onset MFS. Our findings support the existence of a genotype-phenotype correlation between the I1048T substitution and early-onset MFS. Recognition of this relationship has implications for genetic counseling and clinical care. Additionally, exploration of how the I1048T substitution results in a severe phenotype may lead to further insight into the pathophysiology of MFS.
Keywords: FBN1; genotype-phenotype correlation; Marfan syndrome; severe early onset